THE BROADCASTER'S COMMUNICATION WITH LISTENERS ON THE LONDON SCHOOL COMMUNITY RADIO MOVIE TIME PROGRAMME IN KARET TENGSIN VILLAGE - Radjagukguk, Djudjur Luciana; Sidik, Jam'an Al (International Peneliti Ekonomi, Sosial dan Teknologi, 2021)
The large number of radio stations in Jakarta, whether commercial or community radio has posed challenges to London School Radio as a broadcast media in communicating the information to the listeners. The competitive level in the market has driven London School Radio to set up suitable program with the segments, one of them is the communication pattern introduced by the announcer. The announcer has an important role which demands capabilities and skills to communicate with the listeners on matters according to the program and to establish sound communication and interaction which would promote the success of the broadcast. The study applied the concept of communication patterns and explains the types of such communication patterns. There are four types of communication patterns which include wheel, chain and circular communication patterns. The study method used was descriptive method using approach qualitative. Data collection was performed through interview and documentation. The result of study is presented in the form of descriptive paper. In the course of the broadcast, London School Radio announcer especially Movie Time program applies the types of wheel and circular communication patterns. By applying the wheel communication pattern, it is the announcer who communicates the information to the listeners without their feedback, while circular communication allows the announcer to interact with the listeners through social media such as instagram and twitter. There are also times when the announcer interact with the listeners via telephone.